AN EXAMINATION OF CHANGES IN SOME FOREST RESERVES OF KANO STATE, NIGERIA (FUDMA JOURNAL OF SCIENCES, 2023)
Ecosystems in Nigeria are highly vulnerable to many adverse influences deliberate or inadvertent. The main aim of this paper is to examine the current status of the forest reserves in Kano State. Data collection was done using SPOT 5 (2012) satellite image of the area forest reserve and topographical maps were georeferenced in the Arc GIS 10.1 environment. Participatory Rural Appraisal Technique (PRA) was used to gather information on specie changes, dominance and available management practices using a purposive sampling technique drawn from the North central and southern Kano. The data were analysed in the GIS environment and Statistical Package for the Social Sciences (SPSS). The result shows changes of the boundaries of the reserves which indicated a reduction in the areal extents of the reserved areas, variation in tree species density, tree species type, management practices and human interference. Poverty, climate change and medicinal benefits were found to be reasons for encroachment. Parts of some of the reserves have been converted to farmlands for agriculture and settlements. Also, illiteracy and lack of awareness among the greater number of the populace around the protected areas their belief is that wildlife is gift from nature and is owned by everybody hence there is no need restricting its use. The study concluded that there evidence of encroachment and loss of biodiversity in area and recommended for awareness on dangers of deforestation, proper monitoring and management of the reserve areas.
Keywords: Forests, Forest reserves, Species, Change